Seroepidemiological Survey of Anti-Toxoplasma gondii and Anti-Neospora caninum Antibodies in Domestic Cats (Felis catus) in Rolim de Moura, State of Rondônia, North Brazil - Ana Luzia Peixoto Silva; Estefany Ferreira Lima; Geraldo Moreira Silva Filho; Larissa Claudino Ferreira; Beatriz de Andrade Campos; Ividy Bison; Arthur Willian de Lima Brasil; Roberta Nunes Parentoni; Thais Ferreira Feitosa; Vinícius Longo Ribeiro Vilela (Tropical Medicine and Infectious Disease, 2023)
Epidemiological studies on infections by Toxoplasma gondii and Neospora caninum in cats in the North Region of Brazil are scarce. We intended to assess the seroprevalence in cats of anti-T. gondii and anti-N. caninum antibodies, as well as the associated risk factors that may lead them to contract these infections in Rolim de Moura, state of Rondônia, North Brazil. For this, blood serum samples of 100 cats from different regions of the city were evaluated. To assess possible factors associated with infections, epidemiological questionnaires were applied to tutors. The Immunofluorescence Antibody Test (IFAT) was performed for anti-T. gondii (cutoff 1:16) and anti-N. caninum (cutoff 1:50) antibodies. After identifying the positive samples, antibody titration was performed. The results showed the prevalence of 26% (26/100) of anti-T. gondii antibodies, with titration varying between 1:16 to 1:8192. There were no factors associated with the prevalence of anti-T. gondii antibodies in the multivariate analysis in this study. There was no occurrence of seropositive cats for anti-N. caninum. It was concluded that there was a high prevalence of anti-T. gondii antibodies in cats in Rolim de Moura, state of Rondônia, North Brazil. However, the evaluated animals did not present anti-N. caninum antibodies. Therefore, knowing that T. gondii has different transmission forms, we emphasize the importance of spreading more information to the population about cat’s relevance in the T. gondii life cycle and how to avoid the parasite transmission and proliferation.